(3GdYbhO GdLhgQjI aj Md CdaGX GdCRgQjIs - (3Rjf GdOjf efUhQ SHW fGUQ GdOjf GdWHdGhjs; (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO,J (B905 (3g` s ((3fhQGdOjf GdHYdj GdYdej s)
(3ChdgG (B:s
(3CeG HYO, agPG TQM dWja, hJMQjQ TQja, hVYJg Ydi GdebOeI GdCRgQjI aj Yde GdYQHjI GdefShHI s
(3BNQgG (B:s
(3dCf GdhShSI UGOQI ef GdbHjdjf Ydi hLg jdjb Hcd efgeG CLGRfG Gddg SHMGfg hJYGdi ef Pdc s
(3HChdgG Jedc eDQN SfI (B1044(3g`s
(3hBNQg SfI (B1062(3g`s
(3hGdfSNI ebGHdI hHgG fXGe GdJYbjHIs
(3HChdgG JQLeI eNJUQI ddeDda GdWHdGhj s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs